THE EFFECT OF LEADERSHIP STYLE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. BANK BRI KCP LUWU - Fiantika, Widia; Sukri, Sukri; Riyanti, Riyanti (JURNAL EKBIS, 2025)
This study aims to analyze the influence of leadership style and work environment on employee performance at PT. BANK BRI KCP LUWU with a quantitative approach. The sample consisted of 30 employees, using saturated sumption technique. Data were collected using questionnaires and analyzed using multiple linear regression with SPSS 27. The results showed that the work environment had a significant effect on employee performance while leadership style did not. The implications of this study emphasize the importance of creating a conducive work environment and participatory leadership style to increase employee involvement and commitment.